Changes in serum obestatin, preptin and ghrelins in patients with Gestational Diabetes Mellitus - Baykus, Yakup; Gurates, Bilgin; Aydin, Suleyman; Celik, Husnu; Kavak, Burcin; Aksoy, Aziz; Minareci, Yagmur (Pergamon-Elsevier Science Ltd, 2012)
Objectives: The present study aims to establish the levels of acylated ghrelin, desacylated ghrelin, obestatin and preptin, during pregnancy and the postpartum period in pregnant women with Gestational Diabetes Mellitus (GDM) and healthy pregnancy women. Design and methods: The study registered 20 pregnant women with GDM and 20 healthy pregnant women. Fasting venous blood samples were collected from all cases between weeks 24 and 28 of pregnancy and after 24 h postpartum. Hormones were analyzed using ELISA method. Results: Serum acylated ghrelin (p:0.001), desacylated ghrelin (p:0.001), obestatin (p:0.006) and preptin (p:0.001) levels were all found statistically higher in both groups during the postpartum period, when compared to the pregnancy period. A positive correlation was established between desacylated ghrelin and acylated ghrelin (p:0.008), desacylated ghrelin and preptin (p:0.012) and preptin and insulin (p:0.039) in the GDM group during pregnancy. Conclusions: The studied hormones (especially desacylated ghrelin and obestatin) are critical in GDM pathophysiology based on the comparison of measure after and before the delivery. (C) 2011 The Canadian Society of Clinical Chemists. Published by Elsevier Inc. All rights reserved.
Keywords: Gestational Diabetes Mellitus; Obestatin; Preptin; Ghrelin